2021
DOI: 10.1089/cbr.2019.3507
|View full text |Cite
|
Sign up to set email alerts
|

miR-548b Suppresses Melanoma Cell Growth, Migration, and Invasion by Negatively Regulating Its Target Gene HMGB1

Abstract: Background: Melanoma is one of the most aggressive malignancies. Exploration of metastasis-related genes will improve the clinical outcomes of patients with melanoma. Recently, microRNAs (miRNAs) have been implicated in regulating the aggressiveness of melanoma. In the current study, the author demonstrated the expression of miR-548b and its functions in melanoma. Materials and Methods: The expression levels of miR-548b and high mobility group protein 1 (HMGB1) in melanoma specimens and adjacent normal tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Guo et al reported that miR-18a-5p induces proliferation and inhibited apoptosis of melanoma cells by targeting EPHA7 [22]. Fen et al showed that miR-548b inhibits the growth and metastasis of melanoma by negatively regulating HMGB1 [23]. Our results indicate that miR-495-3p targets KPNA2 in melanoma.…”
Section: Discussionsupporting
confidence: 59%
“…Guo et al reported that miR-18a-5p induces proliferation and inhibited apoptosis of melanoma cells by targeting EPHA7 [22]. Fen et al showed that miR-548b inhibits the growth and metastasis of melanoma by negatively regulating HMGB1 [23]. Our results indicate that miR-495-3p targets KPNA2 in melanoma.…”
Section: Discussionsupporting
confidence: 59%
“…HMGB1 is a target of miR-548b, and its expression level is negatively regulated by miR-548b, while the reintroduction of HMGB1 abolishes the inhibiting effects of miR-548b on melanoma cells. All these findings demonstrated that miR-548b might act as a cancer-suppressive miRNA in human melanoma by inhibiting HMGB1, thus suggesting potential systemic and local usefulness [ 15 ]. On a side note, miRNAs have also been evaluated for their role in drug response modulation, in particular for dabrafenib.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miRNAs can affect HMGB1 gene expression, modulating cancer progression. HMGB1 is a direct target of miR-548b, and the expression level of this miRNA can suppress melanoma cells’ growth by targeting the HMGB1 pathway [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the miR-548 family, with over 80 identified miRNAs, regulates the immune process in some diseases, such as cancer ( 88 , 89 ). A large amount studies have shown that miRNA-548 suppresses tumor proliferate by binding WNT2 ( 90 ), murine double minute 2 ( 91 ), metastasis tumor-associated protein-2 ( 92 ), specificity protein 1 ( 93 ), cancerous inhibitor of protein phosphatase 2A ( 94 ), HMGB1 ( 95 ), and so on. Inhibiting or down-regulating miR-548 promotes the tumor proliferation ( 96 ).…”
Section: Discussionmentioning
confidence: 99%